A comparative study of different vibratory stimuli frequencies during orthodontic tooth movement on the secretion of receptor activator of nuclear kappa-b ligand (RANKL)/osteoprotegerin (OPG) ratio - Natchanon Siriphan (Prince of Songkla University, 2021)
Thesis ((Ph.D., Oral Health Sciences))--Prince of Songkla University, 2019